Purificação e caracterização de uma nova metaloprotease da serpente Bothrops moojeni Hoge, 1966(Squamata: Viperidae) com ação na agregação plaquetária - Mayara Ribeiro de Queiroz (2011)
Snake venoms contain a complex mixture of many different biologically active proteins and peptides. The present study aimed to evaluate the proteolytic and biological activities, as well as inhibitory effects on platelet aggregation by a new metalloproteinase from Bothrops moojeni venom. The purification of enzyme, named BmooMPa-II, was carried out through two chromatographic steps (ion-exchange on DEAE-Sepharose and molecular exclusion on Sephacryl S300). BmooMPa-II is a monomeric protein with an apparent molecular mass of 25kDa by SDS-PAGE 14% under reducing conditions. Fibrinogenolytic activity was evaluated by SDS-PAGE 14%. First, BmooMPa-II cleaves the aa-chain of fibrinogen followed by the Bb-chain, and shows no effects on the y-chain. Fibrinogenolytic activity is inhibited by b-mercaptoethanol, EDTA and 1,10-phenantroline. Its optimum temperature and pH for the fibrinogenolytic activity were 30-50 C and pH=8, respectively. Results indicate that this protein probably is a a-fibrinogease and belongs to class PI of SVMPs. BmooMPa-II was devoid of hemorrhagic, coagulant or anticoagulant activities. Furthermore, BmooMPa-II induced no significant edema or hyperalgesia. Histological observations showed that BmooMPa-II caused morphological alterations in liver, lung, kidney and muscle of Swiss mice. BmooMPa-II inhibited platelet aggregation induced by ADP, collagen, ristocetin and epinephrine. When denatured by high temperatures, BmooMPa-II was faster in inhibition of platelet aggregation induced by ADP. Finally, our results suggest the use of BmooMPa-II as a potent inhibitor of platelet aggregation.